If f ( x ) = n = 0 ∑ ∞ ( 2 n + 1 ) ! ( − x 2 ) n such that the equation below is true for integers A and B , find the value of A + B .
∫ 0 2 π f ( x ) f ( 2 π − x ) d x = π B A ∫ 0 π f ( x ) d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Thats exactly the same solution i thought, by the way nice solution sir :)
Log in to reply
I too did the same. But I'm thinking if there is a solution without using \sinc ( x ) function i.e. just using the summation definition of f ( x ) only.
Log in to reply
Yes, it should work. They are identical. It is just that, it may be tedious.
@Chew-Seong Cheong Sir , there is a typo in the 1st line written with blue (It should be du instead of dx)
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = n = 0 ∑ ∞ ( 2 n + 1 ) ! ( − x 2 ) n = n = 0 ∑ ∞ x ( 2 n + 1 ) ! ( − 1 ) n x 2 n + 1 = x sin x
∫ 0 2 π f ( x ) f ( 2 π − x ) d x = ∫ 0 2 π x sin x ˙ 2 π − x sin ( 2 π − x ) d x = ∫ 0 2 π x ( 2 π − x ) sin x cos x d x = ∫ 0 2 π x ( π − 2 x ) sin ( 2 x ) d x Let u = 2 x ⇒ d x = 2 1 d u = ∫ 0 π u ( π − u ) sin ( u ) d u We note that: u 1 + π − u 1 = u ( π − u ) π = π 1 ∫ 0 π ( u 1 + π − u 1 ) sin u d u Since: sin ( π − u ) = sin u = π 1 ∫ 0 π ( u sin u + π − u sin ( π − u ) ) d u Let v = π − u ⇒ d u = − d v = π 1 ( ∫ 0 π u sin u d u − ∫ π 0 v sin v d v ) = π 1 ( ∫ 0 π u sin u d u + ∫ 0 π v sin v d v ) = π 2 ∫ 0 π f ( x ) d x
⇒ A + B = 2 + 1 = 3